Evaluasi Status Keberlanjutan Sistem Pengelolaan Air Limbah Domestik Terpusat Skala Permukiman SANIMAS Citarum Harum di Kota Bandung - Leonardo Sigalingging; Marisa Handajani (Jurnal Serambi Engineering, 2024)
With limited government resources, innovative approaches to sanitation development are needed. One such approach is Community Based Sanitation (SANIMAS), which empowers communities to provide sustainablemanagement. Babakan Sari and Sukapura are two sub-districts in Bandung City that received SANIMAS infrastructure through the Citarum Harum programme. SANIMAS Babakan Sari is located in a densely populated residential area while SANIMAS Sukapura is located in KPAD PINDAD Timur, bothhave not been able to implement sustainable management. This research aims to determine the sustainability status of both SANIMAS, starting with validating the determinants of sustainability withexperts, followed by the Relative Importance Index (RII) test, which is used as the basis for preparing a questionnaire for administrators and users. The results of the scoring were then analysed using the RAPFISH/RAPWASTMAN (Rapid Appraisal for Fisheries/Wastewater Management) software, which showed that SANIMAS Babakan Sari and SANIMAS Sukapura were quite sustainable for the technical aspect with scores of 54.10 and 68.74, respectively. Quite sustainable for institutional aspects with values of 62.32 and 52.04, quite sustainable for environmental aspects with values of 57.62 and 72.06, less sustainable for economic aspects with values of 39.96 and 49.94 and quite sustainable for social aspects culture with values of 53.28 and 63.06.